Butadienochromophoric Chain Substituted Asocyanino Colourants - Afsah, S.A.; Ahmad, Jawaid; Nayyer, S.A. (Asian Journal of Chemistry, 2010)
In present report, certain specific chalcone derivatives and the quaternary bases of thioazoheteroaromatics. was condensed catalytically furnishing a number of butadienochromophoric chain substituted asocyanino colourants (BCCSAC). The colourants were synthesised with a view to evaluate absorptiospectroscopic potentialities and bacteriolytic susceptibilities, caused by diversifications in the nucleo additive and the chain elongative functionalities in the dye molecules.